"This is the anthropologist, and she is sighted": Ethnographic Research with Blind Women - Hammer, Gili (Disability Studies Quarterly, 2013)
Power relations and the researcher's gaze are extremely relevant to the research of blind people, yet rarely documented. Based on three years of anthropological research with blind women in Israel, this paper discusses the methodological considerations raised by the ethnography of blindness and the position of a sighted-woman-researcher in the field. Employing a "reflexive interpretation," the analysis explores the ways in which research with blind participants raises specific questions regarding researcher-researched power relations and social interactions, offering a fresh approach to the discussion of the researcher's "gaze" and knowledge gathered in the field. Focusing on sight and blindness within the research process, the article addresses "sensory knowledge" raised in the field, offering a nuanced account of the ethnographic inquiry as a sensory endeavor, promoting a dialogue among disability studies, anthropology of the senses, feminist disability studies, and qualitative methodology. Key words: blindness; ethnographic research; anthropology; senses; Israel; visual culture; disability; power relations.